2014
DOI: 10.1007/s00464-013-3384-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of internal hernia after gastrectomy with Roux-en-Y reconstruction for gastric cancer

Abstract: The present data suggest the importance of early recognition and treatment of internal hernia, as well as its prevention by closure of mesenteric defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 22 publications
5
28
0
Order By: Relevance
“…Tomographic evaluation is a diagnostic tool in the majority of the cases. Mesenteric torsion and the related stopping of vascular flow, dilated intestinal loops, and acid and dilatation in the biliopancreatic segment are among the findings observed by tomography (5,8). In our case, air images were also observed in the portal system in addition to these findings.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Tomographic evaluation is a diagnostic tool in the majority of the cases. Mesenteric torsion and the related stopping of vascular flow, dilated intestinal loops, and acid and dilatation in the biliopancreatic segment are among the findings observed by tomography (5,8). In our case, air images were also observed in the portal system in addition to these findings.…”
Section: Discussionsupporting
confidence: 71%
“…Many studies have demonstrated that the long-term results of laparoscopic surgery and open surgery in gastric cancers were similar (5,8). Roux-en-Y reconstruction is frequently preferred because of its prevention of anastomotic leaks and reflux in laparoscopic total or subtotal gastrectomy (9).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is thought to be <0.1%. Several studies have also reported higher incidence of internal hernia in the laparoscopic group than in the open group 1 3 9. As the incidence of gastric cancer is significantly lower in the western demographics, laparoscopic gastrectomies are infrequently performed and therefore there is less experience dealing with potential complications such as internal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…A few potential risk factors are found to be associated with the occurrence of internal hernia: (1) laparoscopic surgery reduces the formation of adhesions due to less handling of bowels, (2) weight loss as a result of the surgery reduces the mesenteric fat and accelerates the increase of the size of the mesenteric defect,6 (3) men are more likely to have internal hernia and (4) retrocolic limb Roux-en-Y reconstruction is associated with higher incidence of internal hernia than antecolic limb in a few series 3. Internal hernia secondary to retrocolic technique is associated with higher rates of bowel resections 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation